On the relationship between proteinuria and plasma phosphate (Swiss Medical Weekly, 2017)
Albuminuria is strongly associated with renal and cardiovascular outcomes independently of renal function level. However, the pathophysiology of these associations is debated. In chronic kidney disease (CKD), phosphate retention participates in cardiovascular events and increased cardiovascular mortality. We hypothesised that albuminuria may modulate tubular phosphate handling by the kidney. To verify this hypothesis, we first studied the association between phosphataemia and albuminuria in children with nephrotic syndrome and in adults with CKD. In both cases, higher albuminuria was associated with higher phosphate level, independently of glomerular filtration rate. We further tried to decipher the molecular mechanisms of these observations. Using animal models of nephrotic proteinuria, we could show that albuminuric rats and mice had abnormally elevated sodium-phosphate apical co-transporter expression, despite elevated fibroblast growth factor 23 (FGF23). The FGF23 downstream pathway was inhibited despite elevated FGF23 levels. Klotho protein expression was also lower in proteinuric animals compared to controls. Finally, albumin had no direct effects on phosphate transport in cells. Altogether, we show that albuminuria induces alteration of phosphate tubular handling, independently of glomerular filtration rate. The mechanisms involved appear to include Klotho down-regulation and resistance to FGF23. This observation may link albuminuria to increased cardiovascular disease via altered phosphate handling. Finally, this observation opens up further opportunities to better understand the link between albuminuria, Klotho, FGF23 and phosphate handling.